“A imprensa também governa”: embates jornalísticos e lutas pelo poder entre o jornal o dia e a “imprensa alheia” - Lima, Nilsângela Cardoso (Universidade do Vale do Rio dos Sinos, 2024)
This thesis analyzes the self-reference discourse and the political and partisan activity of O Dia newspaper from 1959 to 1962, a period in which the PTB member Chagas Rodrigues led the state executive. The organization was created in 1951 and, though it discursively presented itself to the reader as “an independent, a political and a news” newspaper facing the political disputes among the parties (PSD, UDN and PTB), it was used as a political weapon according to the interest of its owner, Raimundo Leão Monteiro. To understand the editorial line and the political-partisan activity of O Dia newspaper in the administration of Chagas Rodrigues (PTBUDN), the research corpus is specially composed by articles published by Teresina press from 1959 to 1962, in addition to other sources and documents, such as: periodicals, statistical data, magazines and government messages etc. The research methodology adopted was Discourse Analysis, from the perspective of Michel Foucault (2009; 2010), and the theoretical framework is based on the concepts of Antonio Gramsci (2004), Teun Van Dijk (2008), Serge Berstein (2009), Rodrigo Patto Sá Motta (2014), Barbara H. Rosenwein (2011) and Pierre Bourdieu (2011; 2007). In the light of theoretical and methodological framework, it was verified that O Dia newspaper and the oblivious press were put into service of the struggle for the party political power and their editors assumed the role of agents of PSD, UDN and PTB parties, in an attempt to interfere with the political game and in the construction of reality by establishing values, concepts, classifications, emoticons, making someone believe in what they intended to make visible and known through words, language, combative journalistic discourse and discomposure. A journalistic culture which was engendered in political cultures, manifested itself, above all, through fights, disputes, the symbolic struggle among the editors of O Dia and the other press organizations in Teresina from 1959 to 1962, demonstrating the idea that the “press also governs”.

Esta tesis analiza el discurso autorreferencial y la actuación política y partidista del periódico O Dia en los años 1959 a 1962, periodo en que el petebista Chagas Rodrigues estuvo al frente del ejecutivo estatal. El medio fue creado en 1951 y, aunque se presentaba discursivamente al lector como un periódico "independiente, político y noticioso" frente a las disputas políticas existentes entre los partidos (PSD, UDN y PTB), fue utilizado como arma política de acuerdo con los intereses de su propietario, Raimundo Leão Monteiro. Para comprender la línea editorial y la actuación político-partidista del periódico O Dia durante el gobierno de Chagas Rodrigues (PTB-UDN), el corpus de la investigación está formado principalmente por los artículos publicados en la prensa de Teresina en el periodo de 1959 a 1962, además de otras fuentes y documentos, como: periódicos, datos estadísticos, revistas, mensajes gubernamentales, etc. La metodología de investigación adoptada fue el Análisis del Discurso, desde la perspectiva de Michel Foucault (2009; 2010), y el marco teórico se basa en los conceptos de Antonio Gramsci (2004), Teun Van Dijk (2008), Serge Berstein (2009), Rodrigo Patto Sá Motta (2014), Barbara H. Rosenwein (2011) y Pierre Bourdieu (2011; 2007). A la luz del marco teórico y metodológico, se verificó que el periódico O Dia y la prensa ajena fueron puestos al servicio de la lucha por el poder político-partidista, y sus redactores asumieron el papel de agentes de los grupos pessedistas, udenistas y petebistas, intentando interferir en el juego político y en la construcción de la realidad al instituir valores, conceptos, clasificaciones, emociones, haciendo creer en aquello que pretendían tornar visible y conocido por medio de las palabras, del lenguaje, del discurso periodístico combativo y de las recriminaciones. Una cultura periodística que, engendrada en las culturas políticas, se manifestaba, sobre todo, por las peleas, las disputas, la lucha simbólica entre los redactores de O Dia y los demás medios de comunicación de Teresina entre 1959 y 1962, demostrando la idea de que "la prensa también gobierna".
Keywords: História do Brasil; Jornalismo; Culturas políticas; Comunidades emocionais; Análise do Discurso; O Dia; History of Brazil; Journalism; Political cultures; Emotional communities; Discourse Analysis; Historia de Brasil; Periodismo; Culturas políticas; Comunidades emocionales; Análisis del Discurso; ACCNPQ::Ciências Humanas::História